2009
DOI: 10.1016/j.emospa.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Emotional interactions and an ethics of care: Caring relations in families affected by HIV and AIDS

Abstract: In the context of global processes of economic restructuring, the HIV and AIDS epidemic and socio-cultural constructions of care, many women and young people in low-income households have been drawn into caring roles within the family. Drawing on the literature on an ethics of care, emotional geographies and embodiment, this paper examines the emotional dynamics of the caring process in families affected by HIV and AIDS. Based on the perspectives of both "caregivers" and "care-receivers" from research undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 36 publications
(37 reference statements)
1
67
0
1
Order By: Relevance
“…Caregiver: Historically, the domestic role of caregiver is one in which women “perform unpaid tasks to satisfy the needs of family members or to maintain the home and the family's possessions” (Aguiar & Hurst, 2007; Evans & Thomas, 2009; Lachance-Grzela & Bouchard, 2010). These tasks often include cleaning and cooking, but also intermittent tasks such as car maintenance and yard work as well as emotional work in caring for family members.…”
Section: Traditional Social Roles For Womenmentioning
confidence: 99%
“…Caregiver: Historically, the domestic role of caregiver is one in which women “perform unpaid tasks to satisfy the needs of family members or to maintain the home and the family's possessions” (Aguiar & Hurst, 2007; Evans & Thomas, 2009; Lachance-Grzela & Bouchard, 2010). These tasks often include cleaning and cooking, but also intermittent tasks such as car maintenance and yard work as well as emotional work in caring for family members.…”
Section: Traditional Social Roles For Womenmentioning
confidence: 99%
“…While the bulk of care research focuses on the minority world, a growing literature has explored changing arrangements for the care of chronically ill adults and orphaned children in eastern and southern Africa in response to the devastating impacts of HIV and AIDS on families and communities (Evans and Thomas, 2009;Nyambedha et al, 2003;Robson et al, 2006;Van Blerk and Ansell, 2007a). Research in Tanzania, Kenya, Malawi, Lesotho and Zimbabwe has revealed that young people's caring roles shift along a continuum over time and space (Evans and Becker, 2009;Robson et al, 2006;Skovdal, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Recent geographical literature has revealed the highly embodied nature of such practices that vary in different socio-spatial and temporal contexts (Bondi 2008;Milligan 2005). Research suggests that the emotions experienced by care-givers and care-receivers need to be understood within the broader context of existing socio-cultural relations, gender and age inequalities, stigma and poverty (Evans and Thomas 2009). Tronto (1993) emphasises the interdependence and interconnectedness of human relations, responsibilities and practices of care.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%